The Use of Differentiated Instruction in Achieving Learning Objectives of Islamic Religious Education in the Merdeka Curriculum - Dinana, Muhammad Fahim; Makhfud, Makhfud; Mukhlison, Moch. (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2024)
This paper explores and describes the concept of differentiated instruction according to Carol Tomlinson and the Concept of the Merdeka Curriculum. This paper is based on library research, uses secondary data collected using documentation techniques, and is qualitative-descriptive. The results: the Merdeka Curriculum is the Indonesian curriculum characterized by three things: which are emphasizing the main (essential) material, adding material of character building for the project called building 'Pelajar Pancasila,' and teacher flexibility in conducting learning to fulfill the needs and interests of students. Differentiated instruction, as one of the methods suitable for the Merdeka Curriculum, is a teaching philosophy based on the premise that students learn best when their teachers accommodate their different readiness levels, interests, and learning profiles. Teachers can distinguish at least four classroom elements: content, process, product, and learning environment. Thus, in learning Islamic Education, teachers need to understand the diverse backgrounds of learners in terms of readiness, interests, and learning profiles. Furthermore, teachers differentiate Islamic education in content, process, product, and learning environment.